Mountain Bromo Tourist Satisfaction: The Impact of Sapta Pesona on Revisit Intentions - Mila Diana Sari; Muhammad Syarif Hidayatullah Elmas; Tumini (International Journal of Travel, Hospitality and Events, 2025)
Purpose: The purpose of this research is to analyse the effect of sapta pesona on tourist satisfaction, the effect of sapta pesona on revisit intention, the effect of tourist satisfaction on revisit intention, the effect of sapta pesona on revisit intention through tourist satisfaction. The object of this research is the tourism destination of Mount Bromo. Research methods: Using quantitative explanatory research methods with numerical data collection and analysis using statistical techniques. The population of this research is tourists who have travelled to Mount Bromo before, the number of samples is not known with certainty. Sampling Indonesian tourists aged at least 17 years or more, and were on Mount Bromo when the research took place as many as 112 respondents. The data analysis technique uses descriptive analysis and inferential analysis using Structural Equetion Modelling (SEM) which will be processed using the AMOS program. Results and discussion: The results showed that sapta pesona had a significant positive effect on tourist satisfaction, sapta pesona had a significant positive effect on revisit intentions, tourist satisfaction had a significant positive effect on revisit intentions, and tourist satisfaction was able to mediate the effect of sapta pesona on the revisit intentions of Mount Bromo tourists. Implication: Based on the results of the study, recommendations for future researchers to conduct research with this research model, because there are not many studies that examine the impact of the mediating variable of tourist satisfaction on the effect of Sapta Pesona on revisit intentions.